Meningkatkan Aktivitas, Keterampilan Berpikir Kritis dan Hasil Belajar Peserta Didik Muatan IPA Menggunakan Model Potensi Di SDN Murung Raya 4 Banjarmasin - Muhammad Akmal Yanuari; Fathul Jannah (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The problem that emerged in this study was the low activity and critical thinking skills of students in Natural Sciences content which resulted in not maximizing learning outcomes. This research is a Classroom Action Research (CAR) which is carried out in 3 meetings. The method used was qualitative, the research subjects were class IVB students at SDN Murung Raya 4 Banjarmasin, totaling 16 people, consisting of 8 male students and 8 female students in semester II of the 2022/2023 academic year. The results showed that the activity of educators increased in each meeting until the indicator of success reached a score of 31 with the criteria "Very Good", the activity of students increased in each meeting until it reached a score of 88% with the criteria "Very Active", critical thinking skills increased in each meeting until it reached a score 88% with the criterion "Almost all very high", and students' learning outcomes classically get a score of up to 100% at meeting 3. Based on the results of this study it can be concluded that the use of the POTENSI model can increase activity, critical thinking skills and student learning outcomes SDN Murung Raya 4 Banjarmasin.